Three dimensions of open innovation 1 - Menendez, Marisol (Henry Stewart Talks, 2021)
Explicating Open Innovation, The Importance of Collaboration, 3 Dimensions of Open Innovation, The Mystery of ‘Secret’ and ‘Schizophrenic’ Strategies, The Open Innovation Strategy Canvas, Findings